2019
DOI: 10.1590/1678-992x-2017-0207
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy logic in automation for interpretation of adaptability and stability in plant breeding studies

Abstract: The methods of Annicchiarico (1992) and Cruz et al. (1989) are widely used in phenotypic adaptability and stability analyses in plant breeding. In spite of the importance of these methodologies, their parameters are difficult to interpret. The aim of this research was to develop fuzzy controllers to automate the decision-making process employed by adaptability and stability studies following the methods adopted by Annicchiarico (1992) and Cruz et al. (1989) and check their efficiency using experimental data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…The efficiency of these controllers is due to their powerful ability to model complex human reasoning (Türksen, 2007). Carneiro et al (2019) suggested that this technique may become an important tool in breeding programmes owing to its simplicity and automation capability, especially when a large number of genotypes are evaluated. The current study also demonstrates the utility of automated decision‐making in assessing the adaptability and stability based on a hybrid model of Eberhart & Russell and Lin & Binns modified by Carneiro (1998) for rice.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of these controllers is due to their powerful ability to model complex human reasoning (Türksen, 2007). Carneiro et al (2019) suggested that this technique may become an important tool in breeding programmes owing to its simplicity and automation capability, especially when a large number of genotypes are evaluated. The current study also demonstrates the utility of automated decision‐making in assessing the adaptability and stability based on a hybrid model of Eberhart & Russell and Lin & Binns modified by Carneiro (1998) for rice.…”
Section: Discussionmentioning
confidence: 99%
“…Other contributions refer to different statistical modeling capable of concisely capturing these concepts for use by breeders. Thus, as an example, current computational intelligence methodologies (Nascimento et al 2013;Teodoro et al, 2015) or logic fuzzy (Carneiro et al, 2018;Carneiro et al, 2019) are interesting because they allow for machine learning less subjective interpretations of information or concepts already presented decades ago by Eberhart and Russell (1966) or Lin and Binns (1988). Techniques such as GGE biplot and AMMI use the interaction phenomenon (GxE) and allow, through a series of graphical analyzes, interpretations of environments and genotypes simultaneously where invariance, responsiveness, and similarity of response patterns can be visualized.…”
Section: Fvmentioning
confidence: 99%
“…In this context, to assess adaptability and stability, various statistical methods are used, and differ in statistical principles, biometric procedures, and interpretation of results (Eeuwijk et al 2016). According to Cargnelutti Filho, Perecin, Malheiros and Guadagnin (2007), these methods can be arranged in several classes, such as those based on analysis of variance (Yates & Cochran, 1938;Plaisted & Peterson, 1959;Wricke, 1965), linear regression (Finlay & Wilkinson, 1963;Eberhart & Russell, 1966;Tai, 1971), bi-segmented regression (Verma, Chahal, & Murty, 1978;Cruz, Torres, & Vencovsky, 1989) in non-parametric statistics (Lin & Binns, 1988;Huehn, 1990;Annicchiarico, 1992;Rocha, Muro-Abad, Araujo, & Cruz, 2005;Nascimento et al, 2010;Nascimento et al, 2015), quantile regression (Barroso et al, 2015), bayesian statistics (Couto et al, 2015;Nascimento et al, 2011) and computational intelligence (Nascimento et al, 2013;Teodoro et al, 2015;Carneiro et al, 2018;Carneiro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this limitation, fuzzy logic mathematical modelling can be used to simulate the approximations and uncertainties of human logic (Carneiro et al, 2017;Carneiro et al, 2019) and assign degrees of pertinence to the elements. Fuzzy logic has been used to select common bean cultivars (Carneiro et al, 2017) and to select common bean cultivars for adaptability and stability (Carneiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Linguistic fuzzy logic used with the Sugeno fuzzy controllers for the adaptability and stability of genotypes, based on theEberhart and Russell (1966) method and adapted fromCarneiro et al (2019).…”
mentioning
confidence: 99%